Kontribusi Gaya Kepemimpinan Transformasional Pada Komitment Organisasi (Studi Pada Bpr Di Kota Semarang) - Agung Sedayu; Ririh Dian Pratiwi; Desy Herma Fauza (Universitas Serang Raya, 2018)
One of the problems that employees often face is the employment pressure from their superiors. The impact of the problem includes the increase of employee turnover, the decrease of employee motivation, and the increase of employee absenteeism. Such condition decreases organizational effectivity. Therefore, the first step done by the organization is to increase employee commitment in order to improve effectiveness. To increase employees' commitment, the role of leadership is very important. One of the most popular leadership styles and suitable applied in many setting is the transformational leadership style. It significantly contributes to the improvement of organizational commitment. The leadership has four dimensions: idealized influence, inspirational motivation, intellectual stimulation and individualized consideration. The current study aims to find empirical evidence of the contribution of transformational leadership styles to organizational commitment. The employees of BPR in the city of Semarang are used as samples in the study. The data used are primary data obtained from the distribution of questionnaires to respondents. This study used descriptive analysis techniques and multiple linear regression. The results prove that simultaneously transformational leadership style significantly influence the organizational commitment. Partially inspirational motivation and individualized consideration variables have a significantly positive effect on organizational commitment. However, the idealized influence and intellectual stimulation variable have no effect on organizational commitment. The findings have theoritical and practical implication. From theoritical side, the continued research need to conduct to give clearer description of the two variables relationship. From practical side, leaders of BPR can consider the findings to improve their employee commitment.. Keywords: transformational leadership style and organizational commitment